PENGEMBANGAN MEDIA PEMBELAJARAN AUGMENTED REALITY (AR) UNTUK MENINGKATKAN PEMAHAMAN KONTEKSTUAL SISWA - Ria Iswari; Wulan Raamadhani; Millatul Hayati Suha; Nurul Mahfuza (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to develop an Augmented Reality (AR)-based learning media and determine its effectiveness in improving students’ contextual understanding. The study was motivated by the low level of students’ contextual understanding caused by conventional learning methods that lack the integration of interactive technology in the learning process. AR-based learning media was developed to help students understand learning concepts more concretely, visually, and interactively so that they can relate the material to real-life situations. This research employed the Research and Development (R&D) method using the ADDIE development model, which consists of the stages of Analysis, Design, Development, Implementation, and Evaluation. The research subjects consisted of students divided into experimental and control classes. Data collection techniques included observation, interviews, questionnaires, and contextual understanding tests. The data were analyzed using quantitative and qualitative descriptive techniques through expert validation analysis, student responses, and N-Gain calculations. The results showed that the developed AR-based learning media achieved a very feasible category based on validations from material experts, media experts, and educational practitioners. In addition, the use of AR media proved effective in improving students’ contextual understanding. This was indicated by the higher posttest and N-Gain scores in the experimental class compared to the control class. AR media also increased students’ motivation, engagement, and participation in the learning process because it provided a more interactive and contextual learning experience. Therefore, Augmented Reality (AR)-based learning media can serve as an innovative alternative to support more engaging, meaningful, and technology-relevant learning in the digital education era